ChemInform Abstract: Nanonickel‐Catalyzed Suzuki—Miyaura Cross‐Couplings in Water. Issue 8 (February 2016) - Handa, Sachin; Slack, Eric D.; Lipshutz, Bruce H.
Abstract: In situ generated Ni nanoparticles are used in combination with micellar catalysis for Suzuki—Miyaura cross‐couplings under aqueous conditions.